Proteomic analysis on the regulation of DOPA-melanin synthesis in Talaromyces marneffei. (January 2021) - He, Xiaoyue; Liu, Donghua; Chen, Qicong
Abstract: Background: Yeast form of T.marneffei can produce DOPA-melanin which perform an important role in the pathogen surviving in macrophage. So far, the proteomic associated with melanin synthesis remain unclearly in T.marneffei . Methods: The whole yeast cell proteins were extracted from T.marneffei cultured with or without l -DOPA. Using two-dimensional gel electrophoresis combined with MALDI-TOF mass spectrometry, distinguished proteins were identified between T.marneffei cultured with or without l -DOPA. Furthermore, geldanamycin were used to assess the inhibition effect on T.marneffei melanin production in vitro. Results: 16 distinguished proteins were identified in DOPA-melanized yeast cells, as well as 15 triple-up-expressed proteins and 7 triple-down-expressed proteins in comparison with non DOPA-melanized yeast cells. Of note, proteins differentially expressed proteins were predominantly heat shock proteins. HSP90/60/70 genes expressions increased significantly demonstrated by q-RT-PCR, which was consistent with the proteomics changes. GO analysis showed that the majority of differentially expressed proteins including HSPs(especially HSP90) were found enriched in stress response, cellular process, protein folding, stimuli response and biological process. KEGG pathway analysis showed that proteins were enriched predominantly in phagosome. HSP90 inhibitor(Geldanamycin) inhibited the brown-black pigment production of T.marneffei yeast grown on brain heart infusion agar, as well as the inhibition effect was observed by transmission electron microscope. Conclusions: The results demonstrates that HSP90 palys an essential role in T.marneffei DOPA-melanin synthesis pathway. Highlights: DOPA-melanin plays an important role in virulence and vibility of T.marneffei. Heat shock proteins were found highly expressed in melanined T.marneffei. HSPs, especially HSP90 may have active biological activities in T.marneffei. HSP90 inhibitor(Geldanamycin) inhibited the brown-black pigment production of T.marneffei. HSP90 could be a new target for treatment.